Comparison of photosynthetic induction and transient limitations during the induction phase in young and mature leaves from three poplar clones - Urban, Otmar; Sprtová, Mirka; Kosvancová, Martina; Tomásková, Ivana; Lichtenthaler, Hartmut K; Marek, Michal V (Tree physiology, 2008)
We tested the hypothesis that leaf age affects photosynthetic induction, because conductance to CO2 diffusion usually decreases with increasing leaf age. Photosynthetic inductions, primarily determined by the light modulation of Rubisco activity and stomatal opening, were investigated in both young and mature leaves, as defined by leaf plastochron index (LPI), from three poplar clones: Populus alba L., P. nigra L. and P. x euramericana (Dode) Guinier. In all clones, maximum assimilation rates (A max), maximum stomatal conductance (G Smax) and dark respiration rates (RD) were higher in young leaves (LPI = 3-5) than in mature leaves (LPI = 10-14), and A max decreased from P. alba via P. x euramericana to P. nigra. The clones with high photosynthetic capacity had low induction states 60 s after leaf illumination (IS60; indicating a slow initial induction phase), and required less time to reach 90% photosynthetic induction (T90). In contrast, the clone with the lowest photosynthetic capacity (P. nigra) exhibited high IS60 (high initial induction state) but a long induction time (high T90). A comparison of mature leaves with young leaves revealed significantly (P < 0.01) lower IS60 values in mature leaves of P. nigra only, and significantly higher T90 values in mature leaves of P. alba only. In all clones, young leaves exhibited a lower percentage of maximum transient stomatal limitation during photosynthetic induction (4-9%) compared with mature leaves (16-30%). Transient biochemical limitation, assessed on the basis of the time constants of Rubisco activation (tau), was significantly higher in mature leaves than in young leaves of P. alba; whereas there were no significant differences in tau between young and mature leaves of the other poplar clones. Thus, our hypothesis that leaf age affects photosynthetic induction was confirmed at the level of transient stomatal limitation, which was significantly higher in mature leaves than in young leaves in all clones. For the induction parameters IS60, T90 and tau, photosynthetic induction was more clone-specific and was dependent on leaf age only in some cases, an observation that may apply to other tree species.
Keywords: časové faktory; Cloning, Organism; Photosynthesis; listy rostlin; světlo; oxid uhličitý; Populus; ribulosa-1,5-bisfosfát-karboxylasa; Plant Stomata; Time Factors; klonování organismů; Carbon Dioxide; Light; průduchy rostlin; fotosyntéza; Ribulose-Bisphosphate Carboxylase; Plant Leaves